Impact of COVID-19 on Postgraduate Surgical Education: A Cross-Sectional Study - Joshi, Anip; Paudel, Sujan; Luitel, Prajjwol (Journal of Karnali Academy of Health Sciences, 2024)
Background: The surgical education is different than other disciplines of medical training because the education requires transfer of knowledge along with the surgical skills. Due to COVID-19 pandemic, the conventional method of teaching learning activities had been affected. The aim of this study was to analyze the impact of COVID-19 on post graduate surgical education during the pandemic.Methods: A prospective cross sectional analytical study was conducted at National Academy of Medical Sciences from February 2021 till June 2023. The study population were residents in General Surgery, Orthopaedics and Trauma Surgery, Dental and maxillofacial surgery and Ear, Nose Throat (ENT) /Head and Neck SurgeryPost Graduate programs who required skills training at National Academy of Medical Sciences. The data was collected by structured questionnaire and the data analysis was done using Microsoft Excel program and SPSS software for proportion of impact in different domains compared with Likert scale values. The P value